Educated but Still Borrowing? Financial Literacy and Perceived Ease of Use in Shaping Generation Z's Online Loan Intention in Bandung - Nedia Rahma Yusandi; Nanda Ravenska; Hafid Aditya Pradesa; Nur Imam Taufik (Trescode Green Organization, 2026)
The rapid digital transformation of the financial sector in Bandung City has heightened concerns regarding the proliferation of online loan applications among tech-savvy youth. This study investigates the complex behavioral mechanisms driving Generation Z's intention to use online loans by examining the dual roles of Financial Literacy and Perceived Ease of Use. Grounded in an extended Technology Acceptance Model, this research addresses critical theoretical inconsistencies in prior literature regarding whether financial knowledge universally suppresses credit adoption. Utilizing a sequential explanatory mixed-methods design, the quantitative phase gathered data from 105 self-earning Generation Z respondents through purposive sampling, analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4. This was complemented by a qualitative phase involving in-depth interviews with four key informants to contextualize the statistical outcomes.The empirical findings reveal a striking behavioral dichotomy: Financial Literacy exerts a significant negative effect on usage intention (beta = -0.403, p = 0.043), demonstrating that robust financial knowledge functions as an internal cognitive safeguard that fosters deliberate restraint and risk awareness. Conversely, Perceived Ease of Use emerges as the strongest positive predictor (beta = 0.554, p = 0.000), indicating that frictionless platform designs and rapid disbursement actively bypass risk perception and stimulate borrowing intentions. Together, these two exogenous variables account for 25.0% of the variance in usage intention (R2 = 0.250). Qualitative insights reinforce that while literacy cultivates cautious evaluation, platform accessibility encourages impulsive adoption. To bridge the gap between cognitive restraint and technological convenience, this study introduces the strategic